Kondisi dan Dampak Perbedaan Regulasi Penanganan Narkoba di Beberapa Negara ASEAN - Wear, Elsa Amalia (Fakultas Hukum Universitas Pattimura, 2024)
Introductioan: In this era of globalization, drug abuse and trafficking through smuggling in the Southeast Asian region is increasingly prevalent. Southeast Asia's strategic geographical location makes it an attractive traffic area for drug trafficking syndicates, both transnational and international. Therefore, there is a need for cooperation among ASEAN countries in dealing with this problem. Unfortunately, in terms of drug handling in ASEAN countries, there are still differences in regulations that have an impact on drug handling in the Southeast Asian region.Purposes of the Research: The purpose of this research is to find out how the conditions of differences in drug handling regulations in ASEAN countries and the resulting impacts.Methods of the Research: This research uses normative juridical research methods and the problem approaches used are conceptual approaches, case approaches, and comparative approaches.Novelty of the Research: Based on the results of the research that has been conducted, it is known that there are still differences in regulations between ASEAN countries. This difference can be seen through a comparison between the applicable laws in Indonesia and Malaysia regarding sanctions and the minimum amount of drug possession that can be punished by death. Then the difference in regulations in Thailand which began to legalize the use of marijuana in the health sector as well as in food and beverages. There is also a misalignment that can be seen through differences in the provision of death penalty sanctions. As a result, there is a gap in sanctions that can facilitate narcotics trafficking between countries due to lighter, weaker or less stringent drug handling regulations in one country with another.